Inverse Modeling of GPS Multipath for Snow Depth Estimation-Part II: Application and Validation - Nievinski, Felipe G. [UNESP]; Larson, Kristine M. (Ieee-inst Electrical Electronics Engineers Inc, 2014)
GPS multipath reflectometry (GPS-MR) is a technique that uses geodetic quality GPS receivers to estimate snow depth. The accuracy and precision of GPS-MR retrievals are evaluated at three different sites: grasslands, alpine, and forested. The assessment yields a correlation of 0.98 and an rms error of 6-8 cm for observed snow depths of up to 2.5 m. GPS-MR underestimates in situ snow depth by 10%-15% at these three sites, although the validation methods do not measure the same footprint as GPS-MR.
Keywords: Artificial satellites; electromagnetic reflection; global positioning system; interferometers; multipath channels; radar remote sensing